Uterine artery embolization for management of placenta accreta, a single-center experience and literature review - Abdallah Noufaily; Raja Achou; Mitri Ashram; Miziana Mokbel; Emile Dabaj; Elie Snaifer; Abbas A Chamsuddin (The Arab Journal of Interventional Radiology)
“Morbidly adherent placenta” is a term that describes the continuum of placenta accreta, increta, and percreta. Placenta accreta is the least invasive form, whereas placenta percreta represents a complete penetration of the trophoblast through the uterus that reaches the serosal surface and potentially invades the bladder, rectal wall, and pelvic vessels. Leaving the placenta in situ in the setting of abnormally invasive placenta is now widely practiced. We herein present three cases of abnormal placental implantation diagnosed by antenatal ultrasound and magnetic resonance imaging, in which uterine artery embolization was performed to induce placental infarction and eventually rapid regression but most importantly to minimize peripartum and postpartum bleeding. As we do this, we sought to review the risks of placenta accreta, increta, and percreta and evaluate the role of endovascular therapy to improve maternal outcomes when abnormal placental implantation occurs.